Postpartum Exercise Effect On Breast Milk Production - Khoiriyah, Etika (Jurnal EduHealth, 2022)
Breast milk is the most important source of nutrition for babies, especially until the age of 6 months. Breastfeeding problems need to be addressed immediately, one of which is by giving postpartum exercise. Postpartum exercise is a muscle movement exercise that provides psychological benefits to provide a feeling of relaxation and freshness which can help the hormones aoxytocin and prolactin work optimally to produce breast milk. This study aims to determine the effect of postpartum exercise on increasing milk production. This research is a quasi-experimental study with a one group pre and post test design. A sample of 47 postpartum women respondents with a sampling technique using purposive sampling. Data analysis using the T test. The results showed that after postpartum exercise there was a significant value related to breast milk production with an average value increasing by 102%. The results of data analysis showed that postpartum exercise had an effect on breast milk production with a p value of 0.000 <0.05, so H1 was accepted and H0 was rejected, meaning that there was an effect of postpartum exercise on increased milk production. It can be concluded that there is an effect of postpartum exercise on increasing milk production. The suggestion of this research is that it is hoped that postpartum mothers will receive postpartum exercise education and can be carried out independently so that they can increase milk production and coverage of exclusive breastfeeding.